The Fourth Exploration of the Fundamental Nature of the Universe (London Journal of Research In Science: Natural and Formal, 2024)
The article published earlier discusses space and time, the existence within space, and human existence. If science proves the correctness of zero-dimensional space, the contradictions in modern physics can be resolved. Material philosophy is based on thinking about the material universe. Cosmogony is thinking based on space and existence in space. Based on our ancestors handed down the basic idea of the origin of the universe, in-depth study of the existence of space in the scientific philosophy thinking.
Keywords: Hemodialysis; Chronic renal failure; protein-energy malnutrition; dietary habits.; Information.; Energy; matter; Origin of the Universe; Spirit; Body; Computer and Software; Software Programming; relativity.; Fundamental Nature of the Universe; Zero-dimensional Space; Scientific Philosophy and Reflection; Ancestral Teachings; Force and Time; Space and Existence; Fundamental Force and Thermodynamics ? Scientific Philosophy